A self-medicating scale and questionnaire based drug use survey and the effect of educational intervention among healthcare professional students - S., Radhika M.; S., Mayur S.; Bindra, Kavleen Kaur; Hittalmani, Sushmita G. (International Journal of Basic & Clinical Pharmacology, 2019)
Background: Due to an array of reasons like easy accessibility and awareness about the available drugs, self-medication has steeply increased the already existent drug misuse. As the health professional students are exposed to all the information of drugs, it would be worthwhile to survey if this knowledge is misused to self-medicate. The present study was aimed at determining the impact of educational intervention on the prevalent attitudes and pattern of self-medication among medical, dental and nursing students as they constitute a vulnerable group for such practices. Methods: A total of 360 health professional students participated in the study. A validated questionnaire and self-medication scale (SMS) were used for the survey, before and after the educational workshop. Results: Of the 360 students 70% were females. 93.89% reported practicing self-medication, which reduced to 78.63% after the educational workshops. Average number of self-medication encounters before the workshop was 4.03±0.30. Analgesics were most commonly used. The modified SMS scores were significantly reduced (p<0.0001) after interventional workshops indicating that the enhanced knowledge, increased the reluctance to self-medicate and make students think twice before self-medicating so as to reduce such harmful, casual drug use habits. Educational workshops statistically (p<0.0001) enhanced the participants knowledge of ADRs, OTC drugs, expiry date, package inserts etc. 77.78% nursing students were habituated to at least one drug which was significantly higher (χ2=20.45, p<0.0001) than that of medical and dental students taken together. Conclusions: Educational intervention reduces the evil of self-medication and enhances safe drug use habits among healthcare professional students.